EDUCATION FOR SUSTAINABLE DEVELOPMENT (ESD) MELALUI PEMAHAMAN MASYARAKAT UNTUK MENGURANGI SAMPAH POPOK SEKALI PAKAI DENGAN MENGGUNAKAN POPOK REUSE - Angsoka Dwipayana Marthaliakirana (Florea : Jurnal Biologi dan Pembelajarannya, 2018)
With regard to the environment, waste has a wide impact such as environmental pollution. Development of monitoring in terms of pengelolahan and conservation of river ecosystems needs to be done, the habit of disposing waste disposable diapers is certainly very dangerous to the quality of river water and for the sustainability of the river in the future, because disposable diapers are disposable waste products that contain dirt (stool) and urine from infants, which can have a negative impact on the community's most potent impacts of river pollution. The use of reuse diapers in modern packaging is a product that has long-term economic value because it can be reused, in addition to having medical benefits compared to disposable diapers, is also an important concept to educate the public about the benefits of reuse diapers on the environment. An activity is needed to understand the importance of protecting the environment by reducing the use of disposable diapers, in order to realize Sustainable Development or future sustainable development. The methods used in this research are: lectures through counseling and qualitative descriptive, Counseling is used to give an overview of the effect of disposable diaper use and the solution through the use of reuse diapers, and descriptive qualitative to analyze the outcomes of early and late community understanding before and after being given counseling. The result of the research shows that the society understanding is reduced by 88,2% for the not understood category seen from the first oral test of the end, for the sufficient understanding category increased by 11,7%, the criterion of understanding increased 17,6%, and for category very understand from the previous 0% increased his understanding by 58.9%.